Immunoprevention of triple-negative breast cancer with a novel multivalent vaccine - Lee, Sang Beom; Qian, Jianfei; Pan, Jing; Sei, Shizuko; Wang, Yian; You, Ming (Frontiers in Immunology, 2025)
Triple-negative breast cancer (TNBC) is associated with a poor prognosis due to high recurrence rates and a lack of targeted therapies. Significant challenges in developing efficacious TNBC cancer vaccines are tumor antigen heterogeneity and the risk of antigen-negative variant escape, where target antigen-negative tumor cells can emerge, evading single-antigen vaccine-induced immunity, and drive tumor growth. To address this, we developed TNBCvax, a multi-antigen, multi-peptide vaccine targeting three tumor-associated antigens overexpressed in TNBC: TOP2A, HIF-1α and IGF-1R. The immune preventive effect of TNBCvax was evaluated in both a syngeneic M6 TNBC tumor graft model and the C3(1)/Tag genetically engineered mouse model of TNBC. Our findings demonstrate that TNBCvax significantly reduced tumor development and progression, compared to single-antigen vaccines. TNBCvax induced a robust tumor-associated antigen-specific immune response as evidenced by the increased infiltration of CD3+ T cells, particularly CD8+ T cells, with elevated levels of granzyme B and tumor necrosis factor alpha (TNF-α). TNBCvax was well-tolerated with no significant major organ toxicities, supporting its potential safety in the clinic. In conclusion, TNBCvax offers a promising immunopreventive strategy against TNBC by targeting multiple antigens to provide a broader and more robust immune coverage against TNBC antigens while reducing the risk of antigen-negative variant escape.